2016
DOI: 10.1155/2016/4368326
|View full text |Cite
|
Sign up to set email alerts
|

Research on Cost Information Sharing and Channel Choice in a Dual-Channel Supply Chain

Abstract: Many studies examine information sharing in an uncertain demand environment in a supply chain. However there is little literature on cost information sharing in a dual-channel structure consisting of a retail channel and a direct sales channel. Assuming that the retail sale cost and direct sale cost are random variables with a general distribution, the paper investigates the retailer's choice on cost information sharing in a Bertrand competition model. Based on the equilibrium outcome of information sharing, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…D-S evidence synthesis method is used to conduct information fusion processing for each representative's score. Multiple pieces of evidence (multiple evaluation information) are systematically processed to generate basic probability distribution function and comprehensive evaluation value, as shown in formula (1). Finally, the comprehensive evaluation value weighting of multiple representatives for a certain subject of a supply chain project on all indicators is added up, that is, converted into points.…”
Section: Point Bank Reward Mechanism Of Information Sharingmentioning
confidence: 99%
See 2 more Smart Citations
“…D-S evidence synthesis method is used to conduct information fusion processing for each representative's score. Multiple pieces of evidence (multiple evaluation information) are systematically processed to generate basic probability distribution function and comprehensive evaluation value, as shown in formula (1). Finally, the comprehensive evaluation value weighting of multiple representatives for a certain subject of a supply chain project on all indicators is added up, that is, converted into points.…”
Section: Point Bank Reward Mechanism Of Information Sharingmentioning
confidence: 99%
“…Producers, suppliers, wholesalers, retailers, and e-commerce of agricultural products have mastered agricultural demand, supply, inventory, forecast, logistics, and other information resources. Only through information interconnection and effective sharing can enterprises trust each other, accurately judge the market, timely grasp the demand, adjust sales strategies, improve the overall efficiency of the supply chain, avoid blind supply and supply interruptions caused by information asymmetry, and avoid the phenomenon of "difficult to sell and expensive to buy" of agricultural products [1]. Information sharing is beneficial for the agricultural products supply chain as a whole, but information sharing has great risks for a single subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on channel synergy mainly focused on this field. Scholars propose many channel synergy strategies, such as cooperative advertising strategy [17,18], lateral transshipment strategy [19][20][21], and information sharing strategy [22][23][24]. They all found that in some cases, these channel synergy strategies can improve the performance of manufacturer and retailer simultaneously.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Yao et al [30] explored cost-information sharing in a SC by considering value-added costs as retailers' private information. Liu et al [31] examined the interplay between VCIS and channel choices. Kostamis and Duenyas [32] investigated the value of both cost and demand information sharing.…”
Section: Related Workmentioning
confidence: 99%